2021
DOI: 10.1073/pnas.2023202118
|View full text |Cite
|
Sign up to set email alerts
|

A catalog of tens of thousands of viruses from human metagenomes reveals hidden associations with chronic diseases

Abstract: Despite remarkable strides in microbiome research, the viral component of the microbiome has generally presented a more challenging target than the bacteriome. This gap persists, even though many thousands of shotgun sequencing runs from human metagenomic samples exist in public databases, and all of them encompass large amounts of viral sequence data. The lack of a comprehensive database for human-associated viruses has historically stymied efforts to interrogate the impact of the virome on human health. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(206 citation statements)
references
References 113 publications
8
177
0
1
Order By: Relevance
“…These two Pin-related (COG1961) invertase genes are probably transcribed as an operon, as their coding sequences overlap by 8 nt. A similar arrangement ("in tandem") of two genes encoding homological site-specific DNA recombinases (nearly 80% identity to that described in this study) was also found in the Siphoviridae family viral isolate ctPi910 (BK036829.1) identified from human metagenome [21]. Moreover, many proteins of M. bovirhinis HAZ141_2 prophage-like element, related to phage biology, uncharacterized hypothetical proteins, and others (MBVR141_0934-1035) share significant homology (up to 100%) with their counterparts in viral isolate ctPi910 or in other Siphoviridae viruses (data not shown), pointing to their possible origin.…”
Section: Discussionsupporting
confidence: 82%
“…These two Pin-related (COG1961) invertase genes are probably transcribed as an operon, as their coding sequences overlap by 8 nt. A similar arrangement ("in tandem") of two genes encoding homological site-specific DNA recombinases (nearly 80% identity to that described in this study) was also found in the Siphoviridae family viral isolate ctPi910 (BK036829.1) identified from human metagenome [21]. Moreover, many proteins of M. bovirhinis HAZ141_2 prophage-like element, related to phage biology, uncharacterized hypothetical proteins, and others (MBVR141_0934-1035) share significant homology (up to 100%) with their counterparts in viral isolate ctPi910 or in other Siphoviridae viruses (data not shown), pointing to their possible origin.…”
Section: Discussionsupporting
confidence: 82%
“…The Gut Virome Database (GVD) contains 33,242 viral populations from 1,986 individuals ( 17 ). The Cenote Human Virome Database (CHVD) comprises 45,033 viral operational taxonomic units (vOTUs) from all human body sites ( 18 ). The human Gut Phage Database is currently the largest gut-specific database with 142,809 nonredundant phage genomes assembled from 28,060 metagenomes and 2,898 bacterial genomes, of which 13,429 were classified as complete and a further 27,999 were classified as high quality by CheckV ( 19 , 20 ).…”
Section: Global Human Gut Phage Diversity and Crassphages: Are We Speaking The Same Language?mentioning
confidence: 99%
“…For example, the GVD describes 70 crAssphage populations clustered into 12 viral clusters, but no single population shared across individuals ( 17 ). This is echoed by the analyses of the CHVD and GPD ( 18 , 19 ), with the latter identifying a new clade dubbed Gubaphage that is distantly related to crAss-like phages. These descriptions across multiple publications and databases leave us in a Babel-like situation that, for instance, leaves us pondering what the term “crAssphage” actually means.…”
Section: Global Human Gut Phage Diversity and Crassphages: Are We Speaking The Same Language?mentioning
confidence: 99%
“…In addition, Pf phage may contribute to clinical outcomes in P. aeruginosa infection in patients with cystic fibrosis [ 10 ]. A large number of inovirus-like sequences were obtained from microbial genomes and metagenomes recently, but still have many filamentous phages need to be identified [ 11 , 12 ]. Wild birds as one of the most abundant species carry a large number of viruses.…”
Section: Main Textmentioning
confidence: 99%